Impact of Muscarinic M(3) Receptor Antagonism on the Risk of Type 2 Diabetes in Antidepressant-Treated Patients: A Case-Controlled Study - Tran, Yen-Hao (CNS Drugs, 2017)
BACKGROUND: M(3) muscarinic receptor antagonism has been associated with glucose intolerance and disturbance of insulin secretion. OBJECTIVE: Our objective was to examine the risk of type 2 diabetes mellitus (T2DM) in patients using antidepressants with and without M(3) muscarinic receptor antagonism (AD_antaM(3) and AD_nonantaM(3), respectively). METHODS: We designed a case–control study using a pharmacy prescription database. We selected a cohort of patients who initiated antidepressant use between the ages of 20 and 40 years and who did not receive any anti-diabetic prescriptions at baseline. Cases were defined as those who developed T2DM [i.e., receiving oral anti-diabetic medication, Anatomical Therapeutic Chemical (ATC) code A10B] during the follow-up period (1994–2014), and ten random controls were picked for each case from the cohort of patients who did not develop T2DM. RESULTS: A total of 530 cases with incident T2DM and 5300 controls were included. Compared with no use of antidepressants during the previous 2 years, recent (within the last 6 months) exposure to AD_antaM(3) was associated with a moderately increased risk of T2DM: adjusted odds ratio 1.55 (95% confidence interval 1.18–2.02). In the stratified analyses, this association was dose dependent (>365 defined daily doses) and significant for patients who were in the younger age group (<45 years at the end of follow-up), were female and had no co-morbidity. On the other hand, recent exposure to AD_nonantaM(3) was not associated with a risk for T2DM in any of our analyses. CONCLUSION: Our results suggest that exposure to AD_antaM(3) was associated with the development of T2DM among antidepressant users. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40263-017-0436-x) contains supplementary material, which is available to authorized users.